Optimalisasi Persiapan Pelatihan dan Peningkatan Efisiensi Melalui Kegiatan Administratif di BPSDM Provinsi Kalimantan Tengah - Heni Elia Wati; Abdul Gofur (Transformasi: Journal of Economics and Business Management, 2024)
In the context of training and education (Diklat), optimal preparation is crucial to enhance program efficiency. Effective administrative activities can be the key to success in preparing efficient Diklat programs. This article discusses the importance of optimizing Diklat preparation through good administrative practices. Factors such as planning, organizing, implementing, and monitoring will be outlined as essential steps in achieving these objectives. Additionally, common challenges in optimizing Diklat preparation will be addressed, along with practical suggestions for overcoming them. By optimizing Diklat preparation through administrative activities, organizations can enhance the efficiency of their Diklat programs and achieve better outcomes. Enhancing efficiency in training preparation (Diklat) is a crucial aspect for the Human Resources Development Agency (BPSDM) of Central Kalimantan Province. The objective of this research is to optimize Diklat preparation and improve efficiency through administrative activities in the BPSDM of Central Kalimantan Province. This study utilizes a case study method to analyze the existing Diklat preparation process in the BPSDM of Central Kalimantan Province. Data is collected through interviews, observations, and document analysis related to Diklat administration. Subsequently, the collected data is qualitatively analyzed to identify constraints and opportunities for optimizing Diklat preparation.